2015
DOI: 10.1111/trf.13424
|View full text |Cite
|
Sign up to set email alerts
|

Delayed clamping of the umbilical cord after delivery and implications for public cord blood banking

Abstract: Delayed cord clamping greatly diminishes the volume and TNC count of units collected for a public cord blood bank. Creating an inventory of CBUs with high TNC content may take more time than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 10 publications
(11 reference statements)
1
22
1
Order By: Relevance
“…The effect of delayed clamping on the UCB quality was reported by Allan and colleagues . These authors have indicated some negative correlation between the volume and the TNC amount when clamping is delayed.…”
Section: Highlighted Factorsmentioning
confidence: 76%
See 1 more Smart Citation
“…The effect of delayed clamping on the UCB quality was reported by Allan and colleagues . These authors have indicated some negative correlation between the volume and the TNC amount when clamping is delayed.…”
Section: Highlighted Factorsmentioning
confidence: 76%
“…The effect of delayed clamping on the UCB quality was reported by Allan and colleagues. 72 These authors have indicated some negative correlation between the volume and the TNC amount when clamping is delayed. It is important to take this correlation into account, even though its study has received little attention so far, because delayed clamping has been recommended by pediatricians and may therefore become widespread.…”
Section: Delayed Umbilical Cord Clampingmentioning
confidence: 98%
“…Indeed, DCC cannot be performed in all cases such as deliveries involving neonatal or maternal distress that require more immediate attention to the mother and/or neonate. While DCC significantly impacts the number of units that can be banked, it remains possible to collect units that meet thresholds for banking despite the practice of DCC …”
Section: Discussionmentioning
confidence: 99%
“…Hesitancy arises from the lack of consensus on optimal timing for DCC and theorised risks such as potential volume overload, polycythaemia, jaundice and interruption of collection of blood for cord blood banking 20 42 74. Concerns about delayed resuscitation, thermal care and technical difficulties are being addressed through the development and trialling of new equipment to allow transition to be assisted closer to the mother with the cord intact 75 76.…”
Section: Postnatal Interventionsmentioning
confidence: 99%